(untitled) (SciELO Preprints, 2026)
The concept of sustainable development emerged in the 1970s as an alternative to uncontrolled economic growth. It gained relevance through the 1972 Club of Rome report, which highlighted the need for balancing economic growth, environmental protection, and social justice. Accordingly, the aims of the present study are to map the progress of the literature on the Economic Growth/Climate Change intersection based on the bibliometric analysis of 5919 documents selected in the Scopus and Web of Science databases (1978-2024) in the R software. Based on the results, there was yearly growth by 13.77% in scientific production. China was the leader in number of publications, and it was followed by the United States and the United Kingdom. Environmental Science, Social Sciences, Economics, Energy and Medicine were the main research/production fields. Institutions such as Tsinghua University and the Chinese Academy of Sciences, and authors like Wang S., Bekun F. and Adebayo T. stood out among the other institutions and authors. According to the analysis, there were fast expansion of scientific production, significant international collaboration and gaps that still demand investigation, besides the underscoring of the relevant global collaboration to find sustainable solutions.